El derecho a la integridad personal. Elementos para su análisis - María Isabel Afanador C. (Universidad Autónoma del Estado de México, 2002)
This essay deals with the essential elements of the right to personal integrity, from its historical evolution and legal recognition, to the critical analysis of the gravest examples of its violation, such as torture and the forced disappearance of individuals. The essay focuses not only on the legal aspects of the subject, from the perspective of International Law governing Human Rights, but also includes a political analysis of the current Colombian reality in human rights abuse. The Colombian analysis is viewed from the context of a democratic notion towards human rights, without ignoring the fact that the problem can be analyzed and discussed through different perspectives.